Effects of silicate and carbonate substitution on the properties of hydroxyapatite prepared by aqueous co-precipitation method - Bang, L.T.; Ramesh, Singh; Purbolaksono, Judha; Ching, Yern Chee; Long, B.D.; Chandran, Hari; Ramesh, Subramaniam; Othman, R. (Elsevier, 2015)
This research was conducted to investigate the effects of silicate and carbonate substitutions in hydroxyapatite (HA) on phase retention, physical properties, and in vitro biological response. A wet chemical method was employed to synthesize silicate-substituted HA (Si-HA) and carbonate-substituted HA (CHA). It was shown that the presence of silicate and carbonate ions in the HA lattice increases the specific surface area and Ca/P molar ratio. In addition, the substitution also resulted in a reduction in the crystallinity of the HA powder and promoted better bioactivity of the sintered body. This was confirmed through in vitro cell culture experiment which revealed that the osteoblast cells adhered well on the surface of the ceramic and that ionic-substituted HA exhibited better cell performance than the control HA. (C) 2015 Elsevier Ltd. All rights reserved.